An Overview of Tectonic and Sedimentation Inter-relationship - F. Hasan Sidi; Herman Darman (Ikatan Ahli Geologi Indonesia, 1998)
For more than a century geoscientists had related tectonic to sedimentation by associating geosynclines with thick accumulations of sedimentation. Until the middle of 20th century, sedimentary basins were still rationalized and classified in terms of geosynclinal theory, including the publication of